Az 1939 és 1945 közötti Szlovák Köztársaság államfői tisztsége - Halász, Iván (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The paper deals with the constitutional development of the independent Slovakia between 1939 and 1945. It focuses on the position of the president in the context of the Czechoslovak constitutional tradition and authoritarian challanges, which were typical from the end of the 1930’s. The problem of continuity and discontinuity of the state and law is also an important part of the paper. The Slovak constitution was adopted in 1939. The influence of the Southern-European fascist and authoritarian models were strong during the process of constitution-making, but the Czechoslovak constitution of 1920 also had an impact on the legislator. Although the president of Slovakia, Jozef Tiso arrived from the Slovak Catholic and autonomist movement, he became the symbol of pro-Nazi collaboration during the second world war. Tiso had two positions – he was the Slovak president and paralelly the leader of the Hlinka Slovak People Party, which was a dominant political factor in Slovakia. A special act regulated the position of this party and its leader in the constitutional and political system.